Ultrasonic modulated waves for diagnostics of concrete elements in bending - Meronk, Błażej; Wilde, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper presents the experimental study on the diagnostics of concrete elements with the use of nonlinear acoustic effects. The tests were conducted on a concrete plate subjected to ultrasonic waves modulated with and without an additional low frequency actuator. The experimental results showed that the new method based on the direct modulation of diagnostic ultrasonic waves also provided sub-harmonic frequencies that indicated the presence of damage. The new method does not require a low frequency actuator for generation of low frequency oscillations, and therefore, is more suitable for practical application.